Discrete Time Model for Process Meta Language with Fictitious-Clock - Boštjan Vlaovič; Aleksander Vreže (Applied Sciences, 2022)
Industries like telecommunications, medical, automotive, military, avionics, and aerospace use complex real-time systems. Specification and Description Language (SDL) is one of the leading domain specific languages that is formally defined by international standards and well established in describing such systems. To check system properties abstracted model of the system is prepared in selected modeling language. We use Spin (Simple Promela Interpreter) model checker that is one of the leading tools for verification of complex concurrent and reactive systems. This paper focuses on modeling the SDL timer construct. It is one of the SDL constructs that is not easily modeled with Promela, but is present in many SDL systems. After an overview of the related work we propose a new Discrete Time Model for Promela (DTMP) that is seamlessly integrated in our framework for modeling SDL systems and can be used with the mainstream version of the Spin tool. To the best of our knowledge, this is not possible with the existing solutions. We describe how DTMP can be used to model SDL systems that use timers. Experimental results demonstrate its applicability to non-SDL systems with Fischer’s mutual exclusion protocol and the Parallel Acknowledgment with Retransmission that were used in prior studies. We compare state-space requirements with one of the existing solutions DT Promela and DT Spin. With that, virtues and shortcomings of this high-level solution are exposed. We have shown that DTMP is effective when an extensive range of timer expiration values are used, which is usually the case in real-life SDL systems.